2022
DOI: 10.3389/fimmu.2022.835711
|View full text |Cite
|
Sign up to set email alerts
|

T Lymphocyte Exhaustion During Human and Experimental Visceral Leishmaniasis

Abstract: A key point of immunity against protozoan Leishmania parasites is the development of an optimal T cell response, which includes a low apoptotic rate, high proliferative activity and polyfunctionality. During acute infection, antigen-specific T cells recognize the pathogen resulting in pathogen control but not elimination, promoting the development and the maintenance of a population of circulating effector cells that mount rapid response quickly after re-exposure to the parasite. However, in the case of viscer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 179 publications
(198 reference statements)
0
11
0
Order By: Relevance
“…More in-depth studies targeting other markers of cellular senescence, such as telomere length, are crucial to discriminate between reversible T cell exhaustion and irreversible T cell senescence processes, to disentangle the pathways for future immunotherapeutic approaches. For instance, the high T cell exhaustion levels could be reversed with TIGIT/PD-1 co-blockade using the currently approved immune checkpoint inhibitors in cancer research 4,50 . Especially in di cult-to-cure VL-HIV patients, the associated high toxicity and variable cure rates with such immune checkpoint inhibitors may be within the acceptable range 51 .…”
Section: Discussionmentioning
confidence: 99%
“…More in-depth studies targeting other markers of cellular senescence, such as telomere length, are crucial to discriminate between reversible T cell exhaustion and irreversible T cell senescence processes, to disentangle the pathways for future immunotherapeutic approaches. For instance, the high T cell exhaustion levels could be reversed with TIGIT/PD-1 co-blockade using the currently approved immune checkpoint inhibitors in cancer research 4,50 . Especially in di cult-to-cure VL-HIV patients, the associated high toxicity and variable cure rates with such immune checkpoint inhibitors may be within the acceptable range 51 .…”
Section: Discussionmentioning
confidence: 99%
“…This gene was found to induce B cell differentiation into plasma cell, to be highly expressed in T cell exhaustion and to induce regulatory FOXP3+ T cell to secrete IL10 (33,34). T cell exhaustion is a condition that has been associated with the progression of VL and spleen disorganization (28,35,36), particularly in patients with HIV co-infection (4). The patients with VL of this study showed high expression levels of PRDM1 , CD274 ( PD-L1 ), and CD44 , which also supports the hypothesis of T cell exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent report showed that a 4th booster shot resulted in significant IgG4 subtype elevations [ 124 ], consistent with immunosuppression, potentially predisposing individuals to other diseases. Host immunosuppression (T-cell exhaustion and chronic disease) resulting from protozoa or multiple SARS-CoV-2 variant infections is now well documented [ 125 , 126 , 127 ]. Thus, alternative treatments such as localized mucosal and oral-based vaccines [ 128 ], antivirals [ 129 ], and broad-based antiparasitics or combinations thereof are being considered.…”
Section: Diarylamidines Serine Proteasesmentioning
confidence: 99%